Correlation of dipstick proteinuria with thrombocytopenia and leucopenia and its efficacy predicting the severity of kidney injury in dengue fever - Dr. Medha S; Dr. Kuladeepa Ananda Vaidya; Dr. Sukesh (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Dengue fever is one of the global viral epidemics with more than 50 million cases reported per year with more than 20 thousand deaths every year. Dengue virus infection is transmitted by the bite of Aedes aegypti and Aedes albopictus mosquitoes. Dengue fever manifests as undifferentiated fever, dengue fever (DF), and dengue hemorrhagic fever (DHF).Objective: This study was done in a tertiary care hospital in coastal region of Karnataka, India to correlate dipstick proteinuria with thrombocytopenia and leucopenia and its efficacy in predicting the severity of kidney injury in dengue fever.Methods: The data has been obtained from the patient records of laboratory and medical records section of the hospital. Laboratory testing of patients admitted in the hospital with fever was done. Dengue fever was detected by the positivity to NS1 antigen, IgM and IgG. Patients coming with fever in the out-patient departments were excluded from the study. The hematological parameters and proteinuria were analysed. The Wilcoxon method (nonparametric) and the Student t-test (parametric) were used for statistical analysis. Descriptive statistics were compared using the chi-square test for the variables of gender, age and the clinical forms ofdengue. Hospital ethics committee clearance was obtained before starting the study.Results: Proteinuria is seen to significantly correlate with thrombocytopenia and leucopenia in our study. However there was no significant correlation with leucopenia and thrombocytopenia in our study.Conclusion: Hence injury to the kidney is more likely if there is presence of thrombocytopenia and leucopenia in patients with dengue fever. Thus severity of renal impairment in dengue fever can be predicted by presence of decreased total WBC count and decreased platelet count.